DINAMIKA HEGEMONI BUDAYA DALAM FILM HUMBA DREAMS KARYA RIRI RIZA - Nurmilah Fadilah; Suma Riella Rusdiarti (Universitas Batanghari, 2025)
The film Humba Dreams directed by Riri Riza in 2019 is a drama genre with a duration of 75 minutes raising cultural wealth, natural beauty, and social conflicts found in Sumba society. The film shows the cultural instability caused by Martin returning from the city and the social problems faced by Sumbanese people regarding human trafficking. The existence of cultural instability shows the dynamics of cultural hegemony. This study aims to reveal the level of integral, degenerate, and minimum cultural hegemony contained in the film Humba Dreams (2019). By using qualitative methods to reveal cinematographic elements as signs that indicate the dynamics of cultural hegemony with Pierce's semiotic theory. The researcher divided the sequence of events of the film into 63 sequences to assist in analyzing the data which was then calcified based on the level of hegemony of Gramsci, with the following results: ideal hegemony in Waingapu society, Sumba there were 9 sequences, degenerate hegemony which showed social criticism there were 5 sequences, and Martin character's awareness of ideal hegemony there were 2 sequences. The practice of cultural hegemony contained in Riri Riza's Humba Dreams (2019) is shown in the form of power that applies values and customs based on ancestral heritage, so that it can be interpreted as signs and symbols. The practice of cultural hegemony experiences dynamics, especially in Martin's character